1990
DOI: 10.1093/ptj/70.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helium-Neon Laser Auriculotherapy on Experimental Pain Threshold

Abstract: This study was conducted to examine the effects of helium-neon laser auriculotherapy on experimental pain threshold. Eighty healthy female and male subjects, aged 18 to 39 years, were assigned randomly to one of two treatment groups. Subjects in the Experimental Group (n = 41) received laser stimulation, and subjects in the Control Group (n = 39) received sham stimulation to appropriate acupuncture points on the left ear. Experimental pain threshold at the ipsilateral wrist was determined with an electrical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 1 publication
2
21
0
2
Order By: Relevance
“…Those available studies have focused exclusively upon effects at threshold pain intensities [15-171. Seibert and Gould [151 have reported significant increases in thermal pain threshold after only 35 s of irradiation with a 1 mW He-Ne laser, but Brockhaus and Elger [161 found that irradiation of the Hegu and Jianqian acupuncture points bilaterally for 1 min per point using a similar laser with a peak power of 10 mW produced insignificant effects upon thermal pain threshold. Significant hypoalgesic effects upon electrical pain thesholds at the wrist have also been reported by King and colleagues in a single-blind, placebocontrolled study after laser irradiation (0.03 J/point, -0.3 J/cm2) of auricular acupuncture points in the ipsilateral ear [17]. This notwithstanding, the studies completed to date would appear to be limited in their relevance to clinical practice by their sole use of pain threshold as a means of quantifying analgesic effect, as well as their employment of relatively low treatment dosages.…”
Section: Introductionsupporting
confidence: 56%
“…Those available studies have focused exclusively upon effects at threshold pain intensities [15-171. Seibert and Gould [151 have reported significant increases in thermal pain threshold after only 35 s of irradiation with a 1 mW He-Ne laser, but Brockhaus and Elger [161 found that irradiation of the Hegu and Jianqian acupuncture points bilaterally for 1 min per point using a similar laser with a peak power of 10 mW produced insignificant effects upon thermal pain threshold. Significant hypoalgesic effects upon electrical pain thesholds at the wrist have also been reported by King and colleagues in a single-blind, placebocontrolled study after laser irradiation (0.03 J/point, -0.3 J/cm2) of auricular acupuncture points in the ipsilateral ear [17]. This notwithstanding, the studies completed to date would appear to be limited in their relevance to clinical practice by their sole use of pain threshold as a means of quantifying analgesic effect, as well as their employment of relatively low treatment dosages.…”
Section: Introductionsupporting
confidence: 56%
“…As a consequence, in an effort to establish the positive impressions of survey respondents, we have previously completed several investigations of the hypoalgesic potential of this therapy upon experimental ischaemic pain under controlled laboratory conditions using the pulsed multisource/multiwavelength diode array cited as the most popular treatment unit in the surveys [7,[10][11][12]. In demonstrating a weak but significant treatment-mediated hypoalgesic effect with such therapy, the findings of these ischaemic pain studies corroborated the generally positive results reported in the literature from previous experimental work in animals [13][14][15] and in humans [16,17].…”
Section: Introductionsupporting
confidence: 79%
“…In the carra-control group, the threshold decreased (P < 0.01) by 44-55% of the previous value (352 +-9 g). In the carra-laser and carra-IMC groups, the threshold of the inflamed paw declined (P < 0.01) by only 22-26% and 23-32% of the previous values (352 5 16 g, 358 & 10 g), respectively. In either group, the deficit in the threshold was statistically the same between each other but different (P < 0.01) from the carra-control group.…”
Section: Experiments 1: Inhibitory Effect Of the Lpl-irradiation In Thmentioning
confidence: 76%